CRITICAL STUDY OF THE HADITH “ṢŪMŪ TAṢIḤḤŪ” AND ITS RELATION TO MEDICINE - Dewi Nurul Izzah (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2024)
Fasting in Islam is not only viewed as a spiritual practice but also as an activity that offers health benefits. Many individuals report improvements in their health after observing fasting; however, these claims are often based on personal experiences and religious beliefs. Therefore, more in-depth scientific studies are needed. This article examines the criticisms of the hadith